The Role of Management Accounting Systems in Mediating the Impact of Digital Transformation on Corporate Strategic Decision-Making - Arlan Tahir; Yana Ermawati; Kartim Kartim; Adriani Lande (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effect of Digital Transformation on Strategic Decision-Making and examine the mediating role of Management Accounting Systems in expedition service companies in Jayapura City. The study is grounded in Contingency Theory, Information Processing Theory, and Strategic Management Accounting Theory. Research Method: A quantitative approach with an associative design was employed. The population comprised 120 employees from 36 expedition companies in Jayapura City, of whom 107 were selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. Results and Discussion: The findings reveal that Digital Transformation has a positive and significant influence on Strategic Decision-Making and Management Accounting Systems. Management Accounting Systems also positively affect Strategic Decision-Making and partially mediate the relationship between Digital Transformation and Strategic Decision-Making. These results indicate that the strategic benefits of digital transformation depend on the effectiveness of managerial information systems. Implications: Expedition companies should integrate digital transformation initiatives with Management Accounting Systems to enhance information quality and strategic responsiveness. Future studies may incorporate organizational and technological factors as additional mediators or moderators. Originality: This study highlights the mediating role of Management Accounting Systems in explaining how Digital Transformation enhances Strategic Decision-Making within expedition companies operating in Eastern Indonesia.